IMPACT OF ZINC APPLICATION ON ITS TRANSLOCATION INTO VARIOUS PLANT PARTS OF WHEAT IN A VERTISOL - K. S. KERAM,; B. L. SHARMA,; G. D. SHARMA,; R. K. THAKUR, (The Bioscan, 2014)
The present investigation were conducted for two rabi season 2010-11 and 2011-12 in the field of Department of Soil Science and Agricultural Chemistry, J.N. Krishi Vishwa Vidyalaya, Jabalpur (M.P.) to study the influence of Zn application on its translocation into various plant parts of wheat in a Vertisol. The results revealed that the application of increasing levels of Zn @ 5, 10 and 20 kg ha-1 significantly increased the Zn concentration in root, stem, leaves and earhead of wheat over NPK fertilization alone at different growth stages of wheat. Further, the grain and straw yields as well as harvest index increased with the increasing levels of Zn as compared to NPK alone. The maximum pooled grain yield 4.66 t ha-1 was observed in the treatment 20 kg Zn ha-1, while the minimum pooled grain 3.88 t ha-1 in the control plot (100 % NPK). Thus, the findings of present investigation indicated that the application of Zn eradicates its deficiency in different plant parts of wheat with enhancing the crop yields.